PUBLIC POLICY SEBAGAI ALASAN PEMBATALAN PELAKSANAAN PUTUSAN ARBITRASE INTERNASIONAL DI INDONESIA - Maria Prima Nahak, Anastasia; Keneng, I Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol. 04, No. 01, Februari 2015)
Dispute resolution through arbitration is not a new option for the parties to resolve their dispute in international trade sphere, but the decision is very hard to be implemented. Through normative method, this paper aims to discuss how the arrangement of international arbitration in the positive law of Indonesia and why public policy can be used as an excuse to cancel the arbitration decision. Although international arbitration have been arranged clearly, but the judges still refuse to execute the verdict on the ground that it is contradicted to Indonesian public policy. It can be concluded, with the ambiguity of norms regarding the definition of public policy, international arbitration decision becomes very difficult to be executed in Indonesia and Indonesian arbitration law consequently be doubted by the International community.
Keywords: Court Decision, Arbitration, Execution, Public Policy